The Impact of Empowerment and Work-Life Quality on Job Satisfaction and Its Effect on Organizational Citizenship Behavior - Putri Fristadevi Astuti Nugrahita; Alimuddin Rizal (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine and analyze the effect of empowerment and quality of work life on job satisfaction and its impact on organizational citizenship behavior (OCB). This study uses a quantitative approach, the quantitative approach emphasizes the analysis of numerical data which is processed by statistical methods. The primary data collection method used is by distributing questionnaires to respondents. The test results show that empowerment and quality of work life have a positive and significant effect on job satisfaction. Then empowerment has a negative and insignificant effect on OCB, quality of work life has a positive but not significant effect on OCB and job satisfaction has a positive and significant effect on OCB.